(3ahGFO GdQMdI hfJGFL GdSaQ aj JQGLe aVdGA GdbQf GdMGOj YTQs - (3GdTGaYqj, GdMehj Ke Gdecqj, eUWai Hf aJM Gddg, (B1123 (3g`s ((3eMeO Hf eUWai Hf aJM Gddgs)
(3ChdgG (B:s
(3HSe Gddg MQa GdgeRI ; GdCejf Hf GdUOjb Hf YKeGf CNh GdTjN GdYGQa HGddg JYGdi Gdhdj GHf UGMH GdeQhGM GdUjb GHf EHQGgje Hf CMeO GdTgjO Hf RjO Hf Ydj Hf MSf Hf YWjI s
(3BNQgG (B:s
(3GdMSf Hf SYjO GdjYRQj GdbGVj GdYdGeI Gdabjg GdagGeI GdfHjg CSJGP GdeTGjN cGf ef Cgd GdYbd GdQUjf hGdKHGJ aj GdCeQ hGdTgGeI GdcdjI LjO GdQCj ehKhbG aj LejY CMhGdg Je GdLRA GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\238s
(3EjVGM Gdecfhf (B2\203s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs